Functional Polymorphisms in the p53 Pathway Genes on the Genetic Susceptibility to Zika Virus Teratogenesis - Gomes, Julia A.; Sgarioni, Eduarda; Vieira, Igor A.; Fraga, Lucas R.; Ashton-Prolla, Patrícia; Terças-Tretell, Ana Cláudia P.; da Silva, Juliana H.; Ribeiro, Bethânia F.R.; Galera, Marcial F.; de Oliveira, Thalita M.; Carvalho de Andrade, Maria Denise F.; Carvalho, Isabella F.; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Congenital Zika Syndrome (CZS) occurs in up to 42% of individuals exposed to ZIKV prenatally. Deregulation in gene expression and protein levels of components of the p53 signaling pathway, such as p53 and MDM2, due to ZIKV infection has been reported. Here, we evaluate functional polymorphisms in genes of the p53 signaling pathway as risk factors to CZS. Forty children born with CZS and forty-eight children exposed to ZIKV, but born without congenital anomalies were included in this study. Gestational and sociodemographic information as well as the genotypic and allelic frequencies of functional polymorphisms in TP53, MDM2, MIR605 and LIF genes were compared between the two groups. We found children with CZS exposed predominantly in the first trimester and controls in the third trimester (p<0.001). Moreover, children with CZS were predominantly from families with a lower socioeconomic level (p=0.008). We did not find a statistically significant association between the investigated polymorphisms and development of CZS; however, by comparing individuals with CZS and lissencephaly or without lissencephaly, we found a significative difference in the allelic frequencies of the TP53 rs1042522, which is associated with a more potent p53-induced apoptosis (p=0.007). Our findings suggest that the TP53 rs1042522 polymorphism should be better investigate as a genetic risk factor for the development of lissencephaly in children with CZS.